Innovations in Minimally Invasive Management of Esophageal Atresia and Tracheoesophageal Fistula - Adrian Surd; Rodica Muresan; Carmen Iulia Ciongradi; Lucia Maria Sur; Lia Oxana Usatiuc; Kriszta Snakovszki; Camelia Munteanu; Ioan Sârbu (Gastrointestinal Disorders)
Background and Aims: Esophageal atresia (EA) and tracheoesophageal fistula (TEF) are rare but serious congenital anomalies requiring early surgical intervention. Over the past two decades, minimally invasive surgical (MIS) approaches—particularly thoracoscopic repair—have gained traction, aiming to reduce postoperative morbidity while maintaining surgical efficacy. Objective: This narrative review provides a comprehensive overview of the evolution and current status of MIS techniques for EA/TEF, assessing their clinical outcomes, technical challenges, and implications for patient care. Methods: A structured literature search was conducted to identify clinical studies, reviews, and reports on thoracoscopic, robotic-assisted, and endoscopic approaches to EA/TEF. Emerging adjuncts, including tissue engineering, botulinum toxin use, and magnet-assisted anastomosis, were also reviewed. Results: Thoracoscopic repair has demonstrated comparable anastomotic success rates to open surgery (approximately 85–95%) with significantly reduced rates of musculoskeletal complications, such as scoliosis and chest wall deformities (reported in less than 10% of cases, compared to up to 40% in open approaches). Robotic-assisted and endoscopic-assisted techniques have enabled improved visualization and precision in anatomically challenging cases, although their use remains limited to high-resource centers with specialized expertise. Common postoperative complications include anastomotic stricture (30–50%), gastroesophageal reflux disease (35–70%), and respiratory morbidity, necessitating long-term multidisciplinary follow-up. Recent innovations in simulation-based training and bioengineered adjuncts have facilitated safer MIS adoption in neonates. Conclusions: Minimally invasive techniques have improved the surgical management of EA/TEF, though challenges remain regarding technical complexity, training, and resource availability. Continued innovation and collaborative research are essential for advancing care and ensuring optimal outcomes for affected infants.